Analisis Komprehensif Isu Hak Asasi Manusia Kontemporer Tantangan, Implikasi, dan Prospek Solusi - Endarto, Dwi Wahyu; Nasyruddin, Achmad; Nugraha, Bayu Adhy; Jueni, Jueni; Ikbal, Ikbal; Candra, Firman Adi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article comprehensively analyzes contemporary human rights (HR) issues, highlighting the challenges in HR enforcement, their implications for human dignity, and prospects for innovative solutions. Drawing upon international legal frameworks and philosophical perspectives, this research examines how armed conflicts, humanitarian crises, modern discrimination (including in the digital sphere), and the roles of various actors impact HR protection. A qualitative research method using a literature review and document analysis approach is employed to synthesize findings. The study reveals that the politicization of HR issues, erosion of civil liberties, and new technological challenges present unprecedented complexities. The article concludes with strategic recommendations for strengthening legal frameworks, education, and international cooperation to ensure respect for HR in the future.